Momento cromomagnético anómalo de los quarks - implicaciones para la física hadrónica - López Calderón, Alfonso Aldair (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
In this work, we study the effect of the quarks’ anomalous chromomagnetic moment on the solution of the Schwinger-Dyson and Bethe-Salpeter equations, with an emphasis on its implications for hadronic physics. To this end, these equations are first solved numerically within the rainbow-ladder approximation and then by including the terms associated with the anomalous chromomagnetic moment in the quark-gluon vertex. The solutions are obtained numerically using Fortran, and the main results include the masses of the excited states of the pion and kaon, which show excellent agreement with experimental data, with discrepancies below 3.5 %. The methodology employed allows not only the calculation of the bound state masses but also the extraction of their Bethe-Salpeter amplitudes, opening the possibility of studying form factors in future investigations.

En este trabajo, se estudia el efecto del momento cromomagnético anómalo de los quarks en la solución de las ecuaciones de Schwinger-Dyson y Bethe-Salpeter, con énfasis en sus implicaciones para la física hadrónica. Para ello, se resuelven numéricamente dichas ecuaciones primero en el marco de la aproximación rainbow-ladder y, posteriormente, incluyendo los términos asociados al momento cromomagnético anómalo en el vértice quark-gluon. Las soluciones se obtienen de manera numérica en Fortran, y los resultados principales incluyen las masas de los estados excitados del pion y el kaón, que muestran un excelente acuerdo con los datos experimentales, con discrepancias inferiores al 3.5 %. La metodología empleada permite no solo calcular las masas de los estados ligados, sino también obtener sus amplitudes de Bethe-Salpeter, lo que abre la posibilidad de estudiar factores de forma en futuras investigaciones.
Instituto de Física y Matemáticas. Maestría en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-M-2025-0294; Quark; Masa; Gluon; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19252